Medication adherence in type 2 diabetes mellitus patients: a cross-sectional study - Vieira, Joana Filipa Ferreira (2020)
Objectives: To evaluate the adherence to medication in patients with type 2 Diabetes Mellitus and to assess its impact on the disease-oriented outcomes.Type of Study: Cross-sectional.Location: Porto, Portugal.Population: Patients with type 2 Diabetes Mellitus from a Primary Care Setting.Methods: A convenience sample of patients regularly attending a Primary Care Setting, from July to October 2017, answered anonymously a survey delivered by their family physician. Adherence was assessed by Treatment Adherence Measure questionnaire. Other evaluated variables were demographic and psychosocial factors and disease-oriented outcomes (weight, height, glycated hemoglobin and blood pressure).Results: Eighty-five patients completed the study (54.1% of females) with a mean age of 61.3 years (± 13.8 years). The proportion of patients presenting good adherence to medication was 62.3% (95% CI: 51.8 - 72.9%). The lowest adherence is more common in patients with depressive symptoms (p = 0.004), history of smoking habits (p = 0.019), living alone (p = 0.009) or living without a marital partner (p = 0.039), and it is associated with higher glycated hemoglobin levels (p = 0.004).Conclusions: Poor adherence to medication is a significant problem in the diabetic population, leading to lower glycemic control rates. The identification of its determinants allow us to design a specific intervention in primary care, both in patients’ education and in therapeutic approach, able to improve their health outcomes.